1999
DOI: 10.1073/pnas.96.8.4478
|View full text |Cite
|
Sign up to set email alerts
|

A tradeoff between immunocompetence and sexual ornamentation in domestic fowl

Abstract: Females often select their mates on the basis of the size or intensity of sexual ornaments, and it is thought that such traits are reliable indicators of male quality because the costliness of these traits prevents cheating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
138
4
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(156 citation statements)
references
References 53 publications
(51 reference statements)
11
138
4
2
Order By: Relevance
“…A growing body of evidence indicates that costly sexually selected traits (including testis and ejaculatory traits) can trade-off against other energetically expensive but important characters, such as immune function (Siva-Jothy et al 1998;Verhulst et al 1999;Hosken 2001;Fedorka et al 2004;Simmons & Roberts 2005). Comparative analyses of fruit flies have shown that costly spermatogenesis can trade-off with developmental life histories, such as the onset of reproductive maturity (Pitnick et al 1995;Pitnick 1996;Pitnick & Miller 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that costly sexually selected traits (including testis and ejaculatory traits) can trade-off against other energetically expensive but important characters, such as immune function (Siva-Jothy et al 1998;Verhulst et al 1999;Hosken 2001;Fedorka et al 2004;Simmons & Roberts 2005). Comparative analyses of fruit flies have shown that costly spermatogenesis can trade-off with developmental life histories, such as the onset of reproductive maturity (Pitnick et al 1995;Pitnick 1996;Pitnick & Miller 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In marine isopods, sexual dimorphism in immunity has as yet not been investigated. In many animal species, males have lower immunocompetence than females (Skarstein and Folstad 1996;Kurtz and Sauer 1999;Verhulst et al 1999;Kurtz et al 2000;Ryder and SivaJothy 2000). In invertebrates, one explanation for the sexual dimorphism in immunity may result from diVerent life-history strategies of males and females.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, males were 230 often found with single pairs of worms (whereas single infections were not identified in females in 231 this study) and that level of infection already began to affect body condition. The differences between 232 sexes could be explained by differences in resource allocation, and it has been demonstrated that 233 immunocompetence is often sacrificed in favour of the expression of sexual ornaments, particularly 234 in males (Hamilton & Zuk, 1982;Verhulst et al, 1999). Whether females are able to successfully 235 mount an immune response in the presence of one or two pairs of worms requires further 236 investigation.…”
Section: Birds 218mentioning
confidence: 99%